In-depth investigation of turn-around time of full blood count tests requested from a clinical haematology outpatient department in Cape Town, South Africa - Leonard Mutema; Zivanai Chapanduka; Fungai Musaigwa; Nomusa Mashigo (AOSIS, 2021)
Background: The performance of laboratories can be objectively assessed using the overall turn-around time (TAT). However, TAT is defined differently by the laboratory and clinicians; therefore, it is important to determine the contribution of all the different components making up the laboratory test cycle. Objective: We carried out a retrospective analysis of the TAT of full blood count tests requested from the haematology outpatient department at Tygerberg Academic Hospital in Cape Town, South Africa, with an aim to assess laboratory performance and to identify critical steps influencing TAT. Methods: A retrospective audit was carried out, focused on the full blood count tests from the haematology outpatient department within a period of 3 months between 01 February and 30 April 2018. Data was extracted from the National Health Laboratory Service laboratory information system. The time intervals of all the phases of the test cycle were determined and total TAT and within-laboratory (intra-lab) TAT were calculated. Results: A total of 1176 tests were analysed. The total TAT median was 275 (interquartile range [IQR] 200.0-1537.7) min with the most prolonged phase being from authorisation to review by clinicians (median 114 min; IQR: 37.0-1338.5 min). The median intra-lab TAT was 55 (IQR 40-81) min and 90% of the samples were processed in the laboratory within 134 min of registration. Conclusion: Our findings showed that the intra-lab TAT was within the set internal benchmark of 3 h. Operational phases that were independent of the laboratory processes contributed the most to total TAT.